The Representation of First Nations Art at the Art Gallery of Ontario - Nakamura, Naohiro (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2012)
Canadian art galleries have long been criticized for their poor inclusion of First Nations art, especially historical works. In November 2008, the Art Gallery of Ontario (AGO) opened new Canadian art gallery halls, with 2,000 new acquisitions donated by Ken Thomson. The AGO hired Gerald McMaster, who has tried to make historical First Nations art a key element of the story of Canadian art, as its first Aboriginal curator of the AGO’s Canadian art department. This article reviews several historical events, and the politics and discourse of the representation of First Nations art at the AGO, to examine the success of this new venture, especially in terms of its public appeal.